Music therapy as a pedagogical technology - Rakityanska, L.M.; Ponomarenko, T.V.; Zhuravel, O.V. (Pedagogy of Higher and Secondary Education, 2009)
The article is devoted to the questions content of fenomen musical therapy of modern pedagogical technologies.